2012
DOI: 10.1111/j.1469-8749.2012.04371.x
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic pain, fatigue, and depressive symptoms in adults with spastic bilateral cerebral palsy

Abstract: AIM To investigate the prevalence and co-occurrence of chronic pain, fatigue, and depressive symptoms in adults with spastic bilateral cerebral palsy (SBCP) and explore associations of chronic pain and fatigue with depressive symptoms and daily functioning.METHOD Fifty-six adults with SBCP without severe cognitive impairment participated (35 males, 21 females; mean age 36y 5mo, SD 5y 10mo; Gross Motor Function Classification System level I [13], II [28], III [11], IV [4]). Chronic pain (>3mo), severity and nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
153
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(179 citation statements)
references
References 29 publications
18
153
7
1
Order By: Relevance
“…Likewise, our data in patients with spasticity concurs with previous studies that reported prevalence of pain in stroke to be 19-75%, [26][27][28] 53% in MS, 29 64.9% in SCI 30 and 70% in brain injured patients. 31 The Cochrane Collaboration Systematic Review 32 reported a decrease in shoulder pain after injection of BoNTA; but in contrast, our study provides data on the prevalence of pain at any site in the body (not limited to shoulder pain) in patients experiencing spasticity due to various etiologies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Likewise, our data in patients with spasticity concurs with previous studies that reported prevalence of pain in stroke to be 19-75%, [26][27][28] 53% in MS, 29 64.9% in SCI 30 and 70% in brain injured patients. 31 The Cochrane Collaboration Systematic Review 32 reported a decrease in shoulder pain after injection of BoNTA; but in contrast, our study provides data on the prevalence of pain at any site in the body (not limited to shoulder pain) in patients experiencing spasticity due to various etiologies.…”
Section: Discussionsupporting
confidence: 92%
“…Previous multicenter studies have shown the prevalence of pain in the CP population to be 75-80% 26,27 which is similar to the prevalence of 87% in CP patients with spasticity found in the current study. Likewise, our data in patients with spasticity concurs with previous studies that reported prevalence of pain in stroke to be 19-75%, [26][27][28] 53% in MS, 29 64.9% in SCI 30 and 70% in brain injured patients.…”
Section: Discussionsupporting
confidence: 90%
“…This may have resulted in a higher prevalence than the level found in our study. Some of the other studies focused on specific types of pain, such as musculoskeletal pain 8, or included specific subtypes of CP, for example bilateral spastic 16, both of which could influence the prevalence rate. Furthermore, we included a wide age span, one to 14 years of age, whereas the other studies focused more on pain in adolescents with CP 6.…”
Section: Discussionmentioning
confidence: 99%
“…2 In a recent qualitative study, individuals with CP described difficulty with predicting and managing fatigue from activities of daily living such as walking. 3 When this is combined with other literature that demonstrates individuals with CP experience more fatigue than the general population, 4 the question that arises is: 'Do we know how active these individuals need to be in order to gain appropriate health benefits while mitigating the negative consequences of pain and fatigue?' This question remains unanswered, partially due to the fact that most activities of daily living for these individuals result in increased energy expenditure and effort.…”
mentioning
confidence: 99%
“…2 Fatigue is not unique to children; adults with spastic diplegic CP report significantly higher levels of fatigue and pain than unaffected adults. 3 Maher et al 4 are the first to describe self-reported fatigue in ambulatory children with physical disabilities, so that comparisons can be made with typically developing children and children with other chronic health conditions. By documenting that fatigue levels in a diverse group of young people with physical disabilities are similar to levels in young people with cancer, this study argues that it is time to pay attention to fatigue in children with physical disabilities, and to address this fatigue directly or indirectly by modifying pain, sleep, or physical activity.…”
mentioning
confidence: 99%